A novel non-permanent attachment method for bird-borne tracking devices using 3D-printed clamps - Sindre Molværsmyr; Mie P. Arnberg; Morten Helberg; Arild Breistøl; Signe Christensen-Dalsgaard; Børge Moe; Sveinn Are Hanssen; Norith Eckbo; Marie Curtet; Anna L. K. Nilsson (Journal of Ornithology, 2026)
Collecting GPS positions on bird movements requires secure and efficient attachment methods that maintain animal welfare. For seabirds, one of the most threatened bird groups globally, non-permanent attachment methods are often preferred in short-term studies due to their lower risk of injury, feather damage, or long-term behavioral disruption. However, most available non-permanent solutions, such as tape or temporary adhesives, fail to stay attached for extended periods, often resulting in device loss within days or weeks. Here, we present a novel 3D-printed clamp design for attaching small solar-powered GPS devices to seabirds. The clamp and device were attached to the bird's feathers using only glue, with the clamp specifically designed to interlock with the device. This interlocking mechanism effectively sandwiches the feathers between the clamp and the device, ensuring a secure connection through the use of glue. The clamps were designed to maximize solar panel exposure and minimize premature detachment. We deployed 86 GPS devices on six seabird species across seven locations in Norway from 2023 to 2024, using device-specific clamp variants for attachment to mantle or tail feathers. Devices remained attached for an average of 39 days on mantle feathers (77 birds) and 77 days on tail feathers (four birds), providing sufficient deployment durations to monitor key life stages, such as incubation and chick-rearing. The weight of the clamp structure ranged from 0.5 to 3.2 g, depending on the variant, and emphasis was placed on keeping the total attachment weight as low as possible. The clamps were low-cost, easy to produce using standard 3D printers, and allowed adjustments during application. Our method offers a practical alternative to conventional glue or tape mounts, enabling longer device retention, optimal solar charging, and improved data recovery without resorting to permanent attachment methods such as harnesses. It is particularly well suited for short-term tracking applications over a few weeks to months, such as studying foraging behavior, molt timing, or seasonal movements. Overall, the clamp-based attachment system offers a practical and reliable method for short-term seabird tracking, improving data quality while minimizing impact on the birds.

Divergent migratory strategies of black guillemots from two colonies in the Norwegian Sea - Vegard Sandøy Bråthen; Nina Dehnhard; Annette L. Fayet; Signe Christensen-Dalsgaard; Svein-Håkon Lorentsen; Tycho Anker-Nilssen (Marine Biology, 2026)
Coastal zones are heavily impacted by anthropogenic development. However, they are also important habitats for seabirds, some of which are coastal year-round. We investigated the non-breeding season distribution and activity patterns of black guillemots ( Cepphus grylle ), a year-round coastal seabird species, from two colonies in central/northern Norway over multiple years using geolocator loggers equipped with wet-dry sensors. Migratory behaviour differed among birds from the two colonies. Birds from Røst (67.5°N, 12.0°E) travelled on average further (mean 283 km; max 1008 km) and to more southerly wintering areas than those from Sklinna (65.2°N, 11.0°E), which remained closer to the colony (mean 97 km; max 118 km). Birds from both colonies wintered along coastal stretches of Norway that are characterized by a high islet density and kelp forests, which appear to be important habitat characteristics for black guillemots year-round. Individuals tracked over multiple years showed an intermediate to high repeatability in migration movements. Saltwater immersion data suggested that birds used twilight periods to forage during the winter months, especially at higher latitudes. This suggests that reduced daylength and low temperatures constrained black guillemots to use suboptimal light conditions for foraging. Our study adds important and management-relevant knowledge about the non-breeding season movements and activity patterns of black guillemots.

Proximity to Natural Habitat Is Not Consistently Associated With Pollination Services in Tropical Smallholder Farms: A Systematic Review and Meta‐Analysis - Ennia Bosshard; Mark E. Harrison; Frank van Veen; Chris J. Kettle; Nagaraja Badenahally Chikkarangappa; John E. Banks; Parthiba Basu; Quebin Bosbely Casiá‐Ajché; Bo Dalsgaard; Aditi Dutta; Eunice Enríquez; Natalia Escobedo‐Kenefic; et al. (Ecology Letters, 2025)
Proximity to natural habitat is known to enhance pollination services in large‐scale agriculture, but it remains unclear whether this holds in tropical smallholder farms. These systems are embedded in ecologically complex landscapes, central to global food security, and depend heavily on biodiversity‐derived ecosystem services. We conducted a systematic review and meta‐analysis of 35 studies assessing the relationship between distance to natural habitat and pollinator abundance, species richness, and crop fruit set in tropical smallholder farms. We found no consistent patterns in pollinator abundance and crop fruit set with increasing distance, with relationships highly variable across studies. Similarly variable, yet slightly negative, was the relationship between distance and pollinator species richness. Our findings suggest limited support for the ‘proximity to natural habitat’ hypothesis in tropical smallholder farms, indicating that the inherent complexity of these landscapes may buffer negative effects of distance on pollination. This underscores the importance of maintaining and restoring landscape complexity to sustain biodiversity and ecosystem services such as crop pollination. We also highlight the need for greater methodological consistency and publicly available raw data in future studies to strengthen the evidence base and support management strategies for safeguarding pollination services in tropical smallholder farms.

Decadal decline in forest floor soil organic carbon after clear-cutting in Nordic and Canadian forests - C-F. Johannesson; H. Ilvesniemi; O.J. Kjønaas; K.S. Larsen; A. Lehtonen; J. Nordén; D. Paré; H. Silvennoinen; J. Stendahl; I. Stupak; L. Vesterdal; L. Dalsgaard (Forest Ecology and Management, 2025)

Can dietary C:N ratio influence water quality and microbiology in recirculating aquaculture systems? - Xiaoyu Huang; Sanni L. Aalto; Johanne Dalsgaard; Per Bovbjerg Pedersen (Aquaculture International, 2024)
The potential impacts of diet composition on water quality in recirculating aquaculture systems (RAS) have been studied only to a limited extent. This study examined the effects of different dietary C:N ratios on physiochemical water quality and associated microbiology in 12 pilot scale freshwater RAS with rainbow trout ( Oncorhynchus mykiss ). By adjusting the proportions of protein, carbohydrate, and fat, four diets with different C:N ratios—fully embracing the span observed in commercial diets—were formulated (CN8.5, CN9.3, CN10.0, and CN12.2). Each diet was administered to three separate RAS for 4 weeks at a daily feed loading of 1.67 kg/m 3 make-up water. At the end of the trial (in week 4), concentrations of nitrite-N, nitrate–N, and dissolved COD, and microbial activity were significantly lower and water clarity was simultaneously higher in systems fed the CN12.2 diet as compared to the other diets. Microbial community compositions in system water and biofilter biofilms and the overall microbial abundance in system water were not affected. This was likely due to the molar C:N ratios in system water not correlating to the dietary C:N ratios and being very low (0.27–0.34) throughout all dietary C:N levels, suggesting that microorganisms were carbon limited in all RAS. Altogether, the results demonstrate that changing dietary C:N ratios can affect physicochemical water quality and microbial activity in RAS. In contrast, changing dietary C:N ratios did not affect water C:N ratios or water or biofilter microbial community composition at least within the span of dietary C:N ratios observed for commercial juvenile rainbow trout feeds.

Correction: Feasibility and knowledge gaps to modeling circumpolar seabird bycatch in the Arctic - Ingrid L. Pollet; Yuri Artukhin; Signe Christensen-Dalsgaard; Erpur Hansen; Kathy J. Kuletz; Flemming Ravn Merkel; Guðjón Már Sigurðsson; Hallvard Strøm; Jennifer F. Provencher; Mark L. Mallory (Polar Biology, 2024)

Feasibility and knowledge gaps to modeling circumpolar seabird bycatch in the Arctic - Ingrid L. Pollet; Yuri Artukhin; Signe Christensen-Dalsgaard; Erpur Hansen; Kathy J. Kuletz; Flemming Ravn Merkel; Guðjón Már Sigurðsson; Hallvard Strøm; Jennifer F. Provencher; Mark L. Mallory (Polar Biology, 2024)

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Spatial distribution of selenium-mercury in Arctic seabirds - Marta Cruz-Flores; Jérémy Lemaire; Maud Brault-Favrou; Signe Christensen-Dalsgaard; Carine Churlaud; Sébastien Descamps; Kyle Elliott; Kjell Einar Erikstad; Alexey Ezhov; Maria Gavrilo; David Grémillet; Gaël Guillou; et al. (Environmental Pollution, 2024)

Influence of dietary phosphorus on orthophosphate accumulation in recirculating aquaculture systems with rainbow trout (Oncorhynchus mykiss) - Xiaoyu Huang; Johanne Dalsgaard; Sanni L. Aalto; Ivar Lund; Per Bovbjerg Pedersen (Aquacultural Engineering, 2023)

Reversible mutations in gliding motility and virulence genes: A flexible and efficient phage defence mechanism in Flavobacterium psychrophilum - Jóhanna Jørgensen; Krister Sundell; Daniel Castillo; Liv S. Dramshøj; Natasja B. Jørgensen; Susie B. Madsen; Lotta Landor; Tom Wiklund; Valentina L. Donati; Lone Madsen; Inger Dalsgaard; Mathias Middelboe (Environmental Microbiology, 2022)
Flavobacteria are among the most important pathogens in freshwater salmonid aquaculture worldwide. Due to concerns regarding development of antibiotic resistance, phage therapy has been proposed as a solution to decrease pathogen load. However, application of phages is challenged by the development of phage resistance, and knowledge of the mechanisms and implications of phage resistance is therefore required. To study this, 27 phage‐resistant isolates of F. psychrophilum were genome sequenced and characterized to identify genetic modifications and evaluate changes in phenotypic traits, including virulence against rainbow trout. Phage‐resistant isolates showed reduction or loss of gliding motility, proteolytic activity, and adhesion to surfaces, and most isolates were completely non‐virulent against rainbow trout fry. Genomic analysis revealed that most phage‐resistant isolates had mutations in genes associated with gliding motility and virulence. Reversal of these mutations in a sub‐set of isolates led to regained motility, proteolytic activity, virulence and phage susceptibility. Although costly, the fast generation of phage resistance driven by single, reversible mutations likely represents a flexible and efficient phage defence mechanism in F. psychrophilum . The results further suggest that phage administration in aquaculture systems to prevent F. psychrophilum outbreaks selects for non‐virulent phage‐resistant phenotypes.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Meeting Paris agreement objectives will temper seabird winter distribution shifts in the North Atlantic Ocean - Manon Clairbaux; William W. L. Cheung; Paul Mathewson; Warren Porter; Nicolas Courbin; Jérôme Fort; Hallvard Strøm; Børge Moe; Per Fauchald; Sebastien Descamps; Hálfdán Helgason; Vegard S. Bråthen; et al. (Global Change Biology, 2021)
We explored the implications of reaching the Paris Agreement Objective of limiting global warming to Alle alle , Fratercula arctica , Uria aalge , Uria lomvia and Rissa tridactyla ) using tracking data for ~1500 individuals through resource selection functions based on mechanistic modeling of seabird energy requirements, and a dynamic bioclimate envelope model of seabird prey. Future winter distributions were predicted to shift with climate change, especially when global warming exceed 2°C under a “no mitigation” scenario, modifying seabird wintering hotspots in the North Atlantic Ocean. Our findings suggest that meeting Paris agreement objectives will limit changes in seabird selected habitat location and size in the North Atlantic Ocean during the 21st century. We thereby provide key information for the design of adaptive marine‐protected areas in a changing ocean.

Diverging phenological responses of Arctic seabirds to an earlier spring - Sébastien Descamps; Francisco Ramírez; Sigurd Benjaminsen; Tycho Anker‐Nilssen; Robert T. Barrett; Zofia Burr; Signe Christensen‐Dalsgaard; Kjell‐Einar Erikstad; David B. Irons; Svein‐Håkon Lorentsen; Mark L. Mallory; Gregory J. Robertson; et al. (Global Change Biology, 2019)
The timing of annual events such as reproduction is a critical component of how free‐living organisms respond to ongoing climate change. This may be especially true in the Arctic, which is disproportionally impacted by climate warming. Here, we show that Arctic seabirds responded to climate change by moving the start of their reproduction earlier, coincident with an advancing onset of spring and that their response is phylogenetically and spatially structured. The phylogenetic signal is likely driven by seabird foraging behavior. Surface‐feeding species advanced their reproduction in the last 35 years while diving species showed remarkably stable breeding timing. The earlier reproduction for Arctic surface‐feeding birds was significant in the Pacific only, where spring advancement was most pronounced. In both the Atlantic and Pacific, seabirds with a long breeding season showed a greater response to the advancement of spring than seabirds with a short breeding season. Our results emphasize that spatial variation, phylogeny, and life history are important considerations in seabird phenological response to climate change and highlight the key role played by the species’ foraging behavior.

Circumpolar dynamics of a marine top‐predator track ocean warming rates - Sébastien Descamps; Tycho Anker‐Nilssen; Robert T. Barrett; David B. Irons; Flemming Merkel; Gregory J. Robertson; Nigel G. Yoccoz; Mark L. Mallory; William A. Montevecchi; David Boertmann; Yuri Artukhin; Signe Christensen‐Dalsgaard; et al. (Global Change Biology, 2017)
Global warming is a nonlinear process, and temperature may increase in a stepwise manner. Periods of abrupt warming can trigger persistent changes in the state of ecosystems, also called regime shifts. The responses of organisms to abrupt warming and associated regime shifts can be unlike responses to periods of slow or moderate change. Understanding of nonlinearity in the biological responses to climate warming is needed to assess the consequences of ongoing climate change. Here, we demonstrate that the population dynamics of a long‐lived, wide‐ranging marine predator are associated with changes in the rate of ocean warming. Data from 556 colonies of black‐legged kittiwakes Rissa tridactyla distributed throughout its breeding range revealed that an abrupt warming of sea‐surface temperature in the 1990s coincided with steep kittiwake population decline. Periods of moderate warming in sea temperatures did not seem to affect kittiwake dynamics. The rapid warming observed in the 1990s may have driven large‐scale, circumpolar marine ecosystem shifts that strongly affected kittiwakes through bottom‐up effects. Our study sheds light on the nonlinear response of a circumpolar seabird to large‐scale changes in oceanographic conditions and indicates that marine top predators may be more sensitive to the rate of ocean warming rather than to warming itself.

Diversity of Flavobacterium psychrophilum and the potential use of its phages for protection against bacterial cold water disease in salmonids - D Castillo; G Higuera; M Villa; M Middelboe; I Dalsgaard; L Madsen; R T Espejo (Journal of Fish Diseases, 2012)
Flavobacterium psychrophilum causes rainbow trout fry syndrome (RTFS) and cold water disease (CWD) in salmonid aquaculture. We report characterization of F. psychrophilum strains and their bacteriophages isolated in Chilean salmonid aquaculture. Results suggest that under laboratory conditions phages can decrease mortality of salmonids from infection by their F. psychrophilum host strain. Twelve F. psychrophilum isolates were characterized, with DNA restriction patterns showing low diversity between strains despite their being obtained from different salmonid production sites and from different tissues. We isolated 15 bacteriophages able to infect some of the F. psychrophilum isolates and characterized six of them in detail. DNA genome sizes were close to 50 Kbp and corresponded to the Siphoviridae and Podoviridae families. One isolate, 6H, probably contains lipids as an essential virion component, based on its chloroform sensitivity and low buoyant density in CsCl. Each phage isolate rarely infected F. psychrophilum strains other than the strain used for its enrichment and isolation. Some bacteriophages could decrease mortality from intraperitoneal injection of its host strain when added together with the bacteria in a ratio of 10 plaque‐forming units per colony‐forming unit. While we recognize the artificial laboratory conditions used for these protection assays, this work is the first to demonstrate that phages might be able protect salmonids from RTFS or CWD.

Chemical surface disinfection of eggs of Baltic cod, Gadus morhua L. - J L Overton; M S Bruun; I Dalsgaard (Journal of Fish Diseases, 2010)
The effect of two disinfectants on eggs and larvae of Baltic cod, Gadus morhua , was investigated. The eggs were disinfected for 10 min using various concentrations of either glutaraldehyde (100, 200, 400, 600 and 800 mg L −1 ) or iodophor (10, 50, 100 and 150 mg L −1 ), 1–4‐days post‐fertilization. Bactericidal effect of disinfection, survival to hatching, hatching success and larval abnormalities were assessed. Larval survival was recorded at 5‐, 10‐ and 15‐days post‐hatch (dph). Although Baltic cod eggs have an unusually thin chorion, they could tolerate surface disinfection. A reduction in bacterial growth was observed with increased concentrations of disinfectant (3.0 × 10 7 –1.6 × 10 1 CFU mL −1 ). Abnormalities in newly hatched larvae were not related to disinfection. Survival of the yolk sac larvae was significantly better for eggs treated with 400 mg L −1 glutaraldehyde for 10 min at 10 and 15 dph. Effective disinfection was also recorded using 100 mg L −1 Actomar K30. Egg batch effect rather than initial bacterial concentration, disinfectant type or incubation method determined the survival of the eggs to hatching and survival of larvae. Because of the carcinogenic effect of glutaraldehyde, iodophor is recommended for routine disinfection of cod eggs.

Water recirculation and good management: potential methods to avoid disease outbreaks with Flavobacterium psychrophilum - L Madsen; I Dalsgaard (Journal of Fish Diseases, 2008)
Flavobacterium psychrophilum infections cause high mortality among rainbow trout, Oncorhynchus mykiss , fry in Danish fish farms and hatcheries. Hatcheries based entirely on bore‐hole water recirculation systems have been suggested as a possibility for eliminating F. psychrophilum or at least keeping the amount of this bacterium low. The occurrence of the bacterium in a bore‐hole water recirculation system was compared with a combined bore‐hole water and stream water flow‐through system in a hatchery where outbreaks of rainbow trout fry syndrome caused by F. psychrophilum often occurred. Broodfish, unfertilized and fertilized eggs, eyed eggs and fry, as well as water samples from the tanks/troughs with broodfish/fry, were examined. Suspect yellow bacterial colonies were either confirmed or rejected as F. psychrophilum by growth characteristics and by PCR. As both virulent and less virulent F. psychrophilum isolates are known, isolates were characterized. The isolates were ribotyped and grouped according to ribotyping patterns. Representatives of the groups were serotyped. Fry isolates were very homogeneous whereas isolates from broodfish were heterogeneous, whether the isolates originated from external surfaces of the fish (mucus from skin and gills, haemorrhages and ulcers) or internal organs. Flavobacterium psychrophilum was isolated from broodfish in both water systems; 56% of investigated broodfish from the borehole/flowthrough system and 36% from the recirculation facility harboured the bacterium. In the recirculation system, the bacterium was isolated from fish (ulcers, milt, liver, abdominal cavity) kept in the system for 11 months. Flavobacterium psychrophilum was found in milt and ovarian fluid as well as on the surface of fertilized eggs, but not inside the eggs. Fry also harboured F. psychrophilum , but in the water recirculation system the bacterium was first isolated from the fry after they had been graded. Flavobacterium psychrophilum was found regularly in other parts of the hatchery (outside the recirculation facility), including at the time of grading, suggesting that the occurrence of F. psychrophilum in the fry recirculation facility was due to contamination from the borehole/flowthrough hatchery. It is suggested that the combination of bore‐hole water recirculation systems and good management procedures (including egg disinfection) is a possible method for hatcheries to avoid disease outbreaks due to F. psychrophilum .

Flavobacterium psychrophilum in rainbow trout, Oncorhynchus mykiss (Walbaum), hatcheries: studies on broodstock, eggs, fry and environment - L Madsen; J D Møller; I Dalsgaard (Journal of Fish Diseases, 2005)
The occurrence of Flavobacterium psychrophilum at four rainbow trout hatcheries was investigated to provide more knowledge about the reservoirs and transmission of this bacterium. Broodstock were sampled at stripping (including both unfertilized and fertilized eggs), and the offspring were then sampled at the eyed egg and fry stages. Water and surface samples (e.g. hatchery trays) were also sampled. Flavobacterium psychrophilum was found in ovarian fluid and milt, indicating that broodstock may serve as a reservoir and are latent carriers of the pathogen. Flavobacterium psychrophilum was not found on or inside eggs, but further egg studies will be necessary to elucidate the possibility of vertical transmission of the pathogen. Flavobacterium psychrophilum was isolated from water samples, but only from water that had been in close contact with farmed rainbow trout or eggs. Flavobacterium psychrophilum isolates were characterized and compared with well‐characterized strains, using degradation of elastin, serotype and ribotype profiles. Different ribotypes of F. psychrophilum were found between hatcheries, but a common ribotype A was found at all four hatcheries. Different ribotypes were found in broodstock without clinical disease, whereas only a few ribotypes (mostly ribotype A) were found in diseased fry. The same ribotype A was found in broodstock, in water samples from hatchery trays and in fry, which suggests the possibility of transmission of F. psychrophilum between broodstock and offspring.

Phenotypic and genotypic characterization of Flavobacterium psychrophilum from Finnish fish farms - J Madetoja; M‐L Hänninen; V Hirvelä–Koski; I Dalsgaard; T Wiklund (Journal of Fish Diseases, 2001)
Finnish isolates ( n =37) of Flavobacterium psychrophilum isolated from farmed salmonids were studied using phenotypic and genotypic characteristics. The characteristics of isolates were compared with the characteristics of Swedish and Estonian F. psychrophilum isolates and the type strain, F. psychrophilum NCIMB 1947 T . Multiple isolates from eight disease outbreaks were examined to determine differences between isolates from a single outbreak. The F. psychrophilum isolates represented a biochemically homogeneous group. However, some minor differences in biochemical and physiological characteristics were observed. Seven different antigenic patterns among Finnish isolates were detected and the results suggest a new serotype of F. psychrophilum . Using Cla Ι, Hae ΙΙΙ and Pvu ΙΙ restriction enzymes in ribotyping analyses 13 different genotypes were demonstrated and a possible relationship between serotype Fd and genotype F1 was determined. There were no significant differences between the isolates from Finland, Estonia, Sweden and the type strain of F. psychrophilum .

Bacterial pathogens in rainbow trout, Oncorhynchus mykiss (Walbaum), reared at Danish freshwater farms - I Dalsgaard; L Madsen (Journal of Fish Diseases, 2000)
During a 2‐year period, bacterial fish pathogens were monitored on five rainbow trout, Oncorhynchus mykiss (Walbaum), freshwater farms in Denmark. A total of 1206 fish were examined and 361 bacterial isolates were identified phenotypically. Enteric redmouth disease, furunculosis and rainbow trout fry syndrome/coldwater disease were recorded. Infections caused by Flavobacterium psychrophilum occurred most frequently, but only one outbreak of enteric redmouth disease caused by Yersinia ruckeri serotype O1 and one of furunculosis caused by Aeromonas salmonicida were recorded during the monitoring period. Flavobacterium psychrophilum was isolated on all farms, both during disease outbreaks and from fish without any signs of disease. Serological investigations of F. psychrophilum showed that serotype Th was the dominant serotype found. The serotypes Th and Fd were involved in disease outbreaks of fry and larger fish. All isolates of F. psychrophilum showed proteolytic activities; however, a few isolates, belonging to serotype FpT did not degrade elastin and were not associated with mortality. Increasing resistance problems to oxytetracycline were demonstrated. More than half of the F. psychrophilum isolates showed resistance to oxolinic acid and oxytetracycline. No antibiotic resistant isolates were found among Y. ruckeri and A. salmonicida .

Comparative studies of Danish Flavobacterium psychrophilum isolates: ribotypes, plasmid profiles, serotypes and virulence - L Madsen; I Dalsgaard (Journal of Fish Diseases, 2000)
Ribotyping and plasmid profiling were carried out on 299 Danish Flavobacterium psychrophilum isolates from farmed rainbow trout, Oncorhynchus mykiss (Walbaum). The isolates had been characterized biochemically and serologically in another study. The isolates were very homogeneous, 254 isolates had the same ribotype A (restriction enzyme Eco RI) and 284 isolates harboured one 3.3 kb plasmid. Seventy‐five per cent of the F. psychrophilum isolates had ribotype A, one 3.3 kb plasmid and belonged to either serotype Th or Fd. Virulence studies with representatives of the dominant groups classified such isolates as virulent, and an extra small or large plasmid did not change the virulence level. A relationship between the serotypes Fd and Th, certain ribotypes, and virulence was found. The isolates belonging to serotype FpT and to ribotype B were less virulent. Only a few isolates with other ribotypes were found and these were also less virulent. Isolates that did not have the 3.3 kb plasmid were also less virulent. The virulent isolates all harboured the 3.3 kb plasmid; however, there was no clear correlation between virulence and plasmid content as a 3.3 kb plasmid was also found in less virulent isolates.